EKSTRAKSI KATEKIN DARI BIJI ALPUKAT DENGAN VARIASI PELARUT MENGGUNAKAN METODE MASERASI - Sanjaya, I K. N.; Giantari, N. K. M.; Widyastuti, M. D.; Laksmiani, N. P. L. (Jurnal Kimia (Journal of Chemistry), 2020)
Avocado is one of the fruits favored by many people because of the avocado's taste and content. Avocados contain antioxidants and nutrients such as fat which is 9.8 g / 100 g of fruit flesh. But until now, the use of avocados is still focused on the fruit while other parts such as seeds are underutilized. Catechins are flavonoid compounds contained in avocado seeds. Extraction of catechins in avocado seeds was carried out by maceration method, namely immersion using three variations of solvents namely ethyl acetate, 95% ethanol, and acetone for 24 hours. The results of maceration were filtered and then remaserated for 24 hours to obtain more filtrate, then concentrated with an evaporator rotary vaccum to obtain thick extracts of avocado seeds which were then tested using the TLC-Densitometry method. The results obtained were the highest levels of catechins obtained in maceration using ethyl acetate solvents, with levels of 25.55% b / b. Keywords: avocado seeds, catechins, maceration